Neoplastic meningitis: A retrospective review of clinical presentations, radiological and cerebrospinal fluid findings - Sorrawit Jearanaisilp (2018)
© 2014 Medical Association of Thailand. All rights reserved. Objective: To review the clinical, radiological, and laboratory presentations of patients with neoplastic meningitis.Material and Method: Patients with neoplastic meningitis were recruited by a retrospective search of cerebrospinal fluid (CSF) cytopathological report database of Siriraj Hospital between 1997 and 2006. Clinical information and CSF result of these patients were extracted from their medical records. Neuroimagings were reviewed by a neuroradiologist.Results: The present study revealed 40 cases of neoplastic meningitis, which comprised of 17 cases with carcinomatous meningitis (CM) and 23 lymphoma/leukemia meningitis (LM) cases. In patients with CM, the majority (70%) had adenocarcinoma of lung or breast. Three of 17 cases with unknown primary tumor had carcinomatous meningitis as an initial presentation. In LM, most of the cases (70%) were diagnosed with acute lymphoblastic leukemia (ALL) and non- Hodgkin’s lymphoma (NHL). The most common symptom among patients with CM and LM was headache follow by cranial nerve palsy. In CM cases, CSF cytology was positive in the first specimen in 15 cases (82.35%) and in 22 from 23 cases (95.7%) in LM cases. Overall CSF showed pleocytosis in 36 cases (90%), most of which were lymphocyte predominant. The most common findings from brain imagings were leptomeningeal enhancement and hydrocephalus. Conclusion: The common primary sites were lung and breast cancer in the CM group and ALL and NHL in the LM group. The common symptoms were headache and cranial nerve palsy. Routine CSF examination was abnormal in virtually all cases. Positive CSF cytology was a gold standard for a diagnosis of leptomeningeal metastasis. High index of suspicious and awareness were required to avoid miss diagnosis.